The potential for vaccines against scour worms of small ruminants. Issue 8 (July 2020) - Britton, Collette; Emery, David L.; McNeilly, Tom N.; Nisbet, Alasdair J.; Stear, Michael J.
Graphical abstract: Highlights: Gastrointestinal nematode (GIN) parasites cost Australian sheep and goat industries approximately AUD 450 million per annum. This review details the history of scour worm vaccines, vaccine formulations and routes of delivery. We detail the potential of new 'omics' technologies for identification and validation of vaccine candidate antigens. We propose an integrated program for development, formulation and delivery of a GIN vaccine providing mucosal immunity. Abstract: This review addresses the research landscape regarding vaccines against scour worms, particularly Trichostrongylus spp. and Teladorsagia circumcincta . The inability of past research to deliver scour-worm vaccines with reliable and reproducible efficacy has been due in part to gaps in knowledge concerning: (i) host-parasite interactions leading to development of type-2 immunity, (ii) definition of an optimal suite of parasite antigens, and (iii) rational formulation and administration to induce protective immunity against gastrointestinal nematodes (GIN) at the site of infestation. Recent 'omics' developments enable more systematic analyses. GIN genomes are reaching completion, facilitating "reverse vaccinology" approaches that have been used successfully for the Rhipicephalus australis vaccine for cattle tick, while methods for gene silencing and editing in GIN enable identification and validation of potential vaccine antigens. We envisage that any efficacious scour worm vaccine(s) would be adopted similarly to "Barbervax™" within integrated parasite management schemes. Vaccines would therefore effectively parallel the use of resistant animals, and reduce the frequency of drenching and pasture contamination. These aspects of integration, efficacy and operation require updated models and validation in the field. The conclusion of this review outlines an approach to facilitate an integrated research program.